Characterization of the minimum domain required for targeting budding yeast myosin II to the site of cell division. - Lister, Ida MB.; Tolliday, Nicola J.; Li, Rong. (2016)
Background : All eukaryotes with the exception of plants use an actomyosin ring to generate a constriction force at the site of cell division (cleavage furrow) during mitosis and meiosis. The structure and filament forming abilities located in the C-terminal or tail region of one of the main components, myosin II, are important for localising the molecule to the contractile ring (CR) during cytokinesis. However, it remains poorly understood how myosin II is recruited to the site of cell division and how this recruitment relates to myosin filament assembly. Significant conservation between species of the components involved in cytokinesis, including those of the CR, allows the use of easily genetically manipulated organisms, such as budding yeast (Saccharomyces cerevisiae), in the study of cytokinesis. Budding yeast has a single myosin II protein, named Myo1. Unlike most other class II myosins, the tail of Myo1 has an irregular coiled coil. In this report we use molecular genetics, biochemistry and live cell imaging to characterize the minimum localisation domain (MLD) of budding yeast Myo1.; Springer Open.